2009
DOI: 10.1186/1475-2875-8-225
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and socio-economic factors associated with Plasmodium falciparum infection in children from Equatorial Guinea: results from a nationally representative survey

Abstract: Background: Malaria has traditionally been a major endemic disease in Equatorial Guinea. Although parasitaemia prevalence on the insular region has been substantially reduced by vector control in the past few years, the prevalence in the mainland remains over 50% in children younger than five years. The aim of this study is to investigate the risk factors for parasitaemia and treatment seeking behaviour for febrile illness at country level, in order to provide evidence that will reinforce the EG National Malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 30 publications
6
37
1
2
Order By: Relevance
“…The reported use of mosquito nets by adults was below 42% in Bioko Island in 1996 and 2001, lower than the reported frequency in neighbouring countries [23], but consistent with the 41% reported in 2004 [37]. Inaccessibility to cost-free bed nets was reportedly the main reason given for not using them in our surveys.…”
Section: Discussionsupporting
confidence: 84%
“…The reported use of mosquito nets by adults was below 42% in Bioko Island in 1996 and 2001, lower than the reported frequency in neighbouring countries [23], but consistent with the 41% reported in 2004 [37]. Inaccessibility to cost-free bed nets was reportedly the main reason given for not using them in our surveys.…”
Section: Discussionsupporting
confidence: 84%
“…20 records met our inclusion criteria (table), [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and of these 15 contained the necessary data for inclusion in the quantitative analysis (meta-analysis). Five records were excluded from the quantitative analysis either because Bayesian credible intervals were reported (n=2) or because ORs could not be calculated from the available data (n=3)[A: sentence correct as edited?].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown a positive association while others did not. For example, in a study conducted in Equatorial Guinean children, stunting was positively related to malaria infection, while no significant association was found with wasting and underweight (Custodio et al, 2009). Additionally, in another study conducted in Ghanaian children, Crookston et al (2010), found no significant association between chronic undernutrition and asymptomatic malaria detected by polymerase chain reaction (PCR).…”
Section: Prevalence and Intensities Of Malaria And Soiltransmitted Hementioning
confidence: 98%